Reimagining Fibrosis Research, Outcomes, and Therapeutics Through the Lens of Resolution - Fortier, Sean M.; Redente, Elizabeth F.; Peters-Golden, Marc (Seminars in Respiratory and Critical Care Medicine, 2025)
Tissue fibrosis contributes to progressive organ dysfunction in a multitude of chronic human diseases. Despite decades of ongoing research dedicated to determining the cellular and molecular origins of fibrosis across multiple organs, we continue to lack truly impactful therapies that halt or reverse scarring. This unmet need is especially evident among individuals with fibrotic lung disease, such as idiopathic pulmonary fibrosis (IPF), who frequently succumb to progressive respiratory failure a few years after diagnosis. Current therapies approved for IPF and progressive fibrotic lung diseases emerged from a longstanding drug development paradigm focused on the inhibition of pro-fibrotic drivers of fibrosis. Given that the vast majority of patients with fibrotic lung disease present with already established scarring, the relative paucity of research focused on fibrosis resolution pathways represents a glaring and critical gap in our knowledge. In contrast to the progressive pathologic fibrosis emblematic of IPF, fibrosis evolved as a self-limited wound-healing response to tissue injury, and spontaneous resolution of lung fibrosis is observed in various experimental animal models. These naturally resolving animal models of fibrosis provide an opportunity to define endogenous anti-fibrotic mediators that inhibit multiple drivers of fibrosis and can orchestrate the return of tissue homeostasis. Therapeutic restoration of these endogenous “resolvers”—which are ostensibly disabled in states of pathologic fibrosis—has immense therapeutic potential. In this perspective, we contend that a paradigm shift in our approach toward fibrosis research is needed. Specifically, we propose that pulmonary fibrosis research be reprioritized to collectively focus on mechanisms of fibrosis resolution using rigorous methods designed to unveil, validate, and explore the therapeutic implications of endogenous resolvers.
Keywords: fibrosis resolution; resolvers; drivers; suppressors